Edukasi Hipertensi dan Demonstrasi Pembuatan Obat Tradisional Daun Seledri di Kelurahan Legok Kota Jambi - Maimaznah Maimaznah; Iin Indrawati (3031-8572, 2022)
Hypertension is a chronic disease with increased arterial blood pressure. The city of Jambi is ranked 5th highest, namely 18.82% of the 20 health centers and the one with the highest hypertension cases is Puskesmas Putri Ayu, which is 51.85%. Legok is one of the sub-districts located in the working area of the Puskesmas Putri Ayu Kota Jambi. The data obtained related to hypertension in Legok were 22 people (82%) elderly had hypertension in RT 35, then there were 45 people (48.89%) had hypertension in RT 28, and there were also 8 people (56%) hypertension in RT. 26 Kelurahan Legok. From the results of interviews with heads of families in RT 26, 6 out of 8 families said that families with hypertension did not know much about their illness and home care. There were 10 out of 22 elderly people in RT 35 who were interviewed who said they did not know the problems related to the causes and how to treat hypertension with celery leaf (Apium Graveolens L) traditional medicine which has many benefits, one of which is as an antihypertensive. Several compounds contained in celery have the ability to lower blood pressure, one of which is Apigenin which has properties as a vasodilator which is related to its hypotensive effect. The health problems above need to be solved and followed up. The activities carried out in Kelurahan Legok, Kota Jambi, namely by gathering people, especially those who experience hypertension, then carry out activities. This activity provides knowledge to the public about hypertension and demonstrations of making traditional medicine using celery leaves. The method used is to provide education about hypertension and a demonstration of making traditional medicine with boiled celery leaves. The activity is carried out for 60 minutes with 1 meeting. The result of this activity is that there is an increase in knowledge about hypertension and traditional medicine with boiled celery leaves for people with hypertension in the Kelurahan Legok, Kota Jambi after being given education and demonstrations.